Management and outcome of acral soft-tissue sarcomas - Dean, B J F; Branford-White, H; Giele, H; Critchley, P; Cogswell, L; Athanasou, N; Gibbons, C L M (The bone & joint journal, 2018)
The aim of this study was to evaluate the surgical management and outcome of patients with an acral soft-tissue sarcoma of the hand or foot. We identified 63 patients with an acral soft-tissue sarcoma who presented to our tertiary referral sarcoma service between 2000 and 2016. There were 35 men and 28 women with a mean age of 49 years (sd 21). Of the 63 sarcomas, 27 were in the hands and 36 in the feet. The commonest subtypes were epithelioid sarcoma in the hand (n = 8) and synovial sarcoma in the foot (n = 11). In 41 patients (65%), the tumour measured less than 5 cm in its largest dimension (median size 3 cm (2 to 6)); 27 patients (43%) were diagnosed after inadvertent excision prior to their referral to the specialist sarcoma unit. After biopsy and staging, primary surgical intervention at the sarcoma unit was excision and limb salvage in 43 (68%), partial (digit or ray) amputation in 14 (22%), and more proximal amputation in six (10%). At final follow up, local recurrence had been treated by one partial amputation and six amputations, resulting in a partial amputation rate of 24% and a proximal amputation rate of 19%. The five-year survival rate was 82%. Patients who underwent inadvertent excision showed no statistically significant difference in survival or local recurrence, but were more likely to undergo amputation (p = 0.008). Large tumour size (> 5 cm) was associated with lower survival (p = 0.04) and a higher risk of local recurrence (p = 0.009;). Most acral soft-tissue sarcomas measure less than 5 cm at presentation, indicating that while size can be a useful prognostic factor, it should not be used as a diagnostic threshold for referral. Increased tumour size is associated with a higher rate of local recurrence and reduced survival. Sarcoma excision with limb preservation does not result in an increased risk of local recurrence. Cite this article: Bone Joint J 2018;100-B:1518-23.